Evaluasi Dampak Program Pengelolaan dan Pendayagunaan Pulau Kecil Tahun 2003: Departemen Kelautan dan Perikanan - Sarjono, Haryadi; Notoatmodjo, Budiman (Bina Nusantara University, 2004)
The purpose of this article is to establish a program based on the evaluation during research on ecosystem rehabilitation, fund and capital help, and the use of human resources of local resident on small islands of Puhawang Island (Lampung), Panggang and Pramuka Island (Kepulauan Seribu – DKI Jakarta), and Panjang Island (Banten) during the period of 2001-2002 based on the evolution of programs purpose.